KEBIJAKAN KONEKTIVITAS MARITIM DI INDONESIA - Lukman Adam (Sekretariat Jenderal DPR RI, 2015)
Maritime connectivity must be developed to improve competitiveness and availability of products. Indonesia’s geographical condition, dominated by the sea, needs the improvement of its maritime infrastructure to smoothly convey distribution of goods and the quality of its transportation. Until recently, it is found that there are inefficiencies in the country’s marine transportation. This paper studies the new government’s proposal of “sea toll” and its possible problems in its realization. In more details, the writer evaluates that there will be two main problems in the realization of the maritime connectivity, consisting of internal and external aspects. Meanwhile, for its success, the writer argues that improvements of port facilities, energy suplly, information technology, human resources, and so forth.